2011
DOI: 10.1590/s0031-10492011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia comparada e morfometria de oligoryzomys nigripes e o. flavescens (rodentia, sigmodontinae) no Rio Grande do Sul, Brasil

Abstract: AbstrAct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
(37 reference statements)
2
12
0
5
Order By: Relevance
“…Despite the high diversity of Sigmodontinae and its extensive occupation of different environments, relatively few studies have been conducted on locomotor habits and associated morphological variation in this group. Most of these studies have focused on the ecology of the different forms found in the Atlantic Forest, but few have addressed the anatomy of the postcranial skeleton and its functional morphology (Lund,1840; Stein,1988; Neves,2003; Machado et al,2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high diversity of Sigmodontinae and its extensive occupation of different environments, relatively few studies have been conducted on locomotor habits and associated morphological variation in this group. Most of these studies have focused on the ecology of the different forms found in the Atlantic Forest, but few have addressed the anatomy of the postcranial skeleton and its functional morphology (Lund,1840; Stein,1988; Neves,2003; Machado et al,2011).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the number of recent studies documenting taxonomic variation in appendicular characters at the specific level (e.g., Costa et al,2011; Machado et al,2011), there remains a lack of comparative studies of the appendicular morphology of sigmodontine rodents. This is particularly unfortunate, because most of the rodent fossil remains from Brazilian paleontological sites consist of isolated appendicular fragments generally deposited in caves as owl pellets.…”
Section: Introductionmentioning
confidence: 99%
“…The species Oligoryzomys flavescens (subfamily Sigmodontinae, tribe Oryzomyini) is distributed throughout much of the Brazilian Atlantic Forest, and it can also be found in southern Brazil and parts of Argentina, Paraguay and Uruguay, occupying forest, grassland and anthropogenic habitats (Reis et al, 2006;Miranda et al, 2009). It is a small species, with the body length of adults ranging between approximately 81 and 93 mm, with a color ranging from brown to light brown and thin, long legs with clear foot and interdigital pads (Bonvicino et al, 2008;Machado et al, 2011). Initial field observations indicated that the feet of the juveniles of this species are large in comparison to the rest of the body, which is the origin of this research.…”
Section: Introductionmentioning
confidence: 92%
“…Trata-se de uma maneira de analisar os parâmetros corporais que podem auxiliar na verificação do dimorfismo sexual das espécies 1 . Permite também avaliar a variação intraespecífica, bem como a interespecífica e é um aspecto importante no diagnóstico característico dos organismos.…”
Section: Introductionunclassified